(untitled) (LEARNing Landscapes, 2014)
The author examines how the synchronicity between access and inclusion is emerging in both the K-12 and post-secondary fields. Previously, both agendas have too often been artificially distinguished, it is argued. The article examines the opportunities this creates for the hands-on implementation of inclusive practices in the class, and considers some of the repercussions this organic merge will have at policy level. The author also highlights how the progressive overlap between inclusion and access best practices—such as Universal Design for Learning—benefits the full spectrum of diverse learners.